Development of Enrichment Book of Banjarnegara Folktales in Ngapak Dialect Assisted by Audio Quick Response (QR) Code for High School Students - Ariyani, Dina; Mujimin, Mujimin (Jurnal Paedagogy, 2025)
This study aims to create an enrichment book featuring Banjarnegara folklore in the Ngapak dialect, enhanced with audio Quick Response (QR) code specifically designed for high school students. The research employs a Research and Development (R&D) method, utilizing the ADDIE model. The instruments used in this research include observation sheets, interview guidelines, questionnaires, validation tests, and assessments. Additionally, the data were analyzed using qualitative descriptive analysis techniques, the Likert Scale, and the Wilcoxon Test. The results obtained were the prototype of the Kumpulan Cerita Rakyat Banjarnegara book. The book contains five Banjarnegara folktales including Mula Bukane Banjarnegara, Kawah Sikidang, Asal Usule Kalibening, Mitos Jalatunda, and Ki Ageng Giring written in ngapak dialect Javanese. In addition to featuring illustrations, the book includes an audio QR code to enhance its innovation and differentiation. According to the results of the expert validation test, the product received a total score of 382, indicating it is feasible. Furthermore, the effectiveness test results showed a significance value of 0.00, confirming its effectiveness.